Transactions for trading used electric vehicle batteries: theoretical underpinning and information systems design principles - Sebastian Bräuer; Florian Plenter; Benjamin Klör; Markus Monhof; Daniel Beverungen; Jörg Becker (Business Research, 2020)
Proof-of-concept projects have demonstrated that used electric vehicle batteries (EVBs), after their removal from electric vehicles due to insufficient performance, can be repurposed for less demanding applications. It is expected that numerous batteries will be available for repurposing in the 2020s. However, the information asymmetries and transaction costs of trading used EVBs have remained unexplored, as have principles that guide the design of information systems that support the trade. Based on existing literature and in-depth interviews with battery experts, we conceptualize two key transactions for trading used EVBs. We then identify potential information asymmetries and transaction costs based on new institutional economic theory and propose five design principles that information systems should implement to address these information asymmetries and transaction costs. Subsequent research can build on our results to further frame the economic properties of trading used EVBs and to design information systems in line with new institutional economic theory.
Keywords: 650; EVB Repurposing; Second life; Second use; New institutional economics; Design science